(untitled) (Global Journal of Science Frontier Research, 2016)
Bioaccumulation ability of the grass Chrysopogon aciculatus for the heavy metals cobalt (Co), manganese(Mn), copper(Cu), lead(Pb), chromium(Cr), cadmium(Cd), nickel(Ni), and zinc( Zn) was studied. Samples of soil and the grass (fresh) were collected from No. 1 Alu avenue off Ahmad Bello way, Nasarawa L. G. A. of Kano State, Nigeria. Collection was made in August to September, 2015. Samples of the grass collected were washed with tap water, carefully separated into roots and shoots, dried at room temperature to a constant weight and grounded. This was then digested using aqua-regia (HNO 3 and HCl) in the ratio of 1:3 and analyzed for the said metals using AAS. The soil was equally treated using same reagent and analyzed for same metals.